A Study of Accountants' Judgments With Respect to the Provision of Consolidated Financial Statements. - Day, Ron; Psaros, Jim (Abacus, 1996)
The release of the Australian Accounting Standards Board AASB 1024, Consolidated Accounts, in September 1991 represents a fundamental shift in concept, criteria and approach. The Standard is based on the entity concept and adopts 'capacity to control' as the sole criterion for identifying related entities for the purpose of preparing consolidated financial statements. A conceptual (substance-over-form) approach is used to implement the control criterion. In essence, this approach requires accountants to make professional judgments about the existence of control based on the substance of group structures and arrangements rather than their legal form. Concerns about the subjectivity and possible variability of accountants' judgments cast some doubt on the operational effectiveness of the conceptual approach. In response to these concerns, this paper reports the results of an experiment that examines the consolidation judgments accountants make in response to a number of hypothetical scenarios. The purpose of this paper, therefore, is to provide some insights into the likely quality and reliability of consolidation judgments under the conceptual approach adopted by AASB 1024. The results indicate that accountants can be expected to exhibit broad consensus in their consolidation judgments. In addition, an analysis of the variables suggests that the degree of share ownership is the most significant factor in making such judgments. Nevertheless, other factors including the composition of the board of directors, the existence of a special arrangement, and interactions with the other variables also proved to be significant. Overall the study provides tentative support for the conceptual approach adopted in AASB 1024.